2021
DOI: 10.3390/en14061793
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Access to Electricity: An Assessment of the Energy and Power Generation Potential from Biomass Waste Residues in Tanzania

Abstract: Tanzania has a high rural population, of which many rely on off-grid diesel generators to produce electricity. The focus of this paper is to assess if the waste biomass residues in Tanzania have sufficient energy potential to produce renewable electrical energy for small-scale electricity generation using off-grid diesel generators coupled with anaerobic digestion (AD) and/or gasification. The gaseous fuel produced can then be used to substitute diesel fuel used in small-scale dual fuel diesel gen-sets; thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 44 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Gasification is a thermochemical activity that combines the interaction of biomass in the presence of air, oxygen, or steam to generate a combination of gases, including hydrogen (H 2 ) methane (CH 4 ), carbon monoxide (CO), carbon dioxide (CO 2 ), nitrogen (N 2 ), and hydrocarbons called as syngas, producer gas, or synthetic gas, the quantities of which vary [14,15]. e primary goal of the process of gasification is to maximize the yield of vapors while minimizing the production of unreacted char and hydrolysable hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gasification is a thermochemical activity that combines the interaction of biomass in the presence of air, oxygen, or steam to generate a combination of gases, including hydrogen (H 2 ) methane (CH 4 ), carbon monoxide (CO), carbon dioxide (CO 2 ), nitrogen (N 2 ), and hydrocarbons called as syngas, producer gas, or synthetic gas, the quantities of which vary [14,15]. e primary goal of the process of gasification is to maximize the yield of vapors while minimizing the production of unreacted char and hydrolysable hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Because unattractive compounds such as tars are destroyed during gas combustion, the syngas used is barely cleansed. If the tar is not overwhelmed and the majority of the particulate matter is removed from the gasifier, syngas can also be used in combustion engines [14,15]. Gas turbines encourage high-efficiency integrated gasification-combined cycle power, while good gas cleaning is required.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of syngas in diesel generators will widen the fuel choices and availability in those developing countries with abundant biomass to produce syngas [1]. Fossil fuels require large-scale refining and transport infrastructure, and are also subject to geopolitical events that can affect social stability, price and availability [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that in Tanzania, the access to electricity is limited to 35.6% of the total 56.32 million population as of 2018 [1]. One location, a village called Luxmanda, is not connected to the grid, but survives on the available DC microgrid which provides power to some few loads [2].…”
Section: Introductionmentioning
confidence: 99%